Delayed Polarization Saturation Induced Superior Energy Storage Capability of BiFeO3‐Based Ceramics Via Introduction of Non‐Isovalent Ions. Issue 14 (10th January 2023) - Zhao, Jinghao; Hu, Tengfei; Fu, Zhengqian; Pan, Zhongbin; Tang, Luomeng; Chen, Xiqi; Li, Huanhuan; Hu, Jiawen; Lv, Ling; Zhou, Zhixin; Liu, Jinjun; Li, Peng; et al.
Abstract: Electrostatic capacitors are emerging as a highly promising technology for large‐scale energy storage applications. However, it remains a significant challenge to improve their energy densities. Here, an effective strategy of introducing non‐isovalent ions into the BiFeO3 ‐based (BFO) ceramic to improve energy storage capability via delaying polarization saturation is demonstrated. Accordingly, an ultra‐high energy density of up to 7.4 J cm −3 and high efficiency ≈ 81% at 680 kV m −1 are realized, which is one of the best energy storage performances recorded for BFO‐based ceramics. The outstanding comprehensive energy storage performance is attributed to inhibiting the polarization hysteresis resulting from generation ergodic relaxor zone and random field, and generating highly‐delayed polarization saturation with continuously‐increased polarization magnitudes with the electric field of supercritical evolution. The contributions demonstrate that delaying the polarization saturation is a consideration for designing the next generation of lead‐free dielectric materials with ultra‐high energy storage performance. Abstract : Delayed polarization saturation of BFO‐based ceramic achieves remarkable capacitive energy storage performance, including ultra‐high energy density of 7.4 J cm −3 and high efficiency ≈81% at 680 kV cm −1 . The contributions demonstrate that delaying the polarization saturation is a consideration for designing the next generation of lead‐free dielectric materials with ultra‐high energy storage performance.